The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/advs.201901279
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐3 nm Intermetallic Ordered Pt3In Clusters for Oxygen Reduction Reaction

Abstract: Previous works have found that the surface atomic structure and composition of catalysts play critical roles in the electrocatalytic performance of Pt-based catalysts. [5][6][7] Accordingly, nanoalloys with various atomic arrangement style including controlled composition or shape, core-shell structure, heterostructure, hollow structure and ordered structure have been designed and proved to be effective ways to modify the catalytic performance of Pt-based catalyst. [8][9][10][11][12] Furthermore, well-designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…[51][52][53][54] Contrary to the disordered alloys,t he ordered intermetallics have specific arrangements of Pt and transition metals with ap recise crystal lattice properties.O rdered alloy provides biaxial strain with tension in one particular direction and compression in the other, which endows remarkable changes in electrochemical behavior of PtM alloys. [39] Different kind of ordered alloys have been reported with significantly improved structural and electrocatalytic properties than their counter disordered alloys,e .g., binary PtCo, [55][56][57] PtCo 3 , [58] PtFe, [45] PtIn, [59] CoPt, [60] ternary PtNiCo. [61] Controlling particle size in intermetallics is highly desirable,a s most of the intermetallics are prepared by annealing at high temperature,where avoiding particle aggregation is challenging.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[51][52][53][54] Contrary to the disordered alloys,t he ordered intermetallics have specific arrangements of Pt and transition metals with ap recise crystal lattice properties.O rdered alloy provides biaxial strain with tension in one particular direction and compression in the other, which endows remarkable changes in electrochemical behavior of PtM alloys. [39] Different kind of ordered alloys have been reported with significantly improved structural and electrocatalytic properties than their counter disordered alloys,e .g., binary PtCo, [55][56][57] PtCo 3 , [58] PtFe, [45] PtIn, [59] CoPt, [60] ternary PtNiCo. [61] Controlling particle size in intermetallics is highly desirable,a s most of the intermetallics are prepared by annealing at high temperature,where avoiding particle aggregation is challenging.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…After acid treatment, the alloying effect of PtIn core makes the catalyst possess excellent ORR performance, with negligible decay of structure and activity after the 20,000 cycles ADT. The DFT calculations demonstrate that the introduction of In atoms can also optimize the oxygen adsorption energy on the NP surface, which further enhances the ORR activity of the catalyst [168]. Its stability is even better than that of the conventional ORR catalysts such as PtFe, PtCo and PtNi NPs in terms of the MEA test.…”
Section: Intermetallic Compounds Of Pt With Non-fenton Activity Elementsmentioning
confidence: 96%
“…They found Pt 3 Cu to exhibit the highest mass activity amongst all other compositions attributed to the formation of Cu oxide species and redissolution/redeposition of the Cu species during the voltage cycling [44] . DFT calculations showed that ordered Pt 3 In is more favourable for ORR since ΔG 0 reaches more closer to the peak of the volcano plot after incorporation of ordered indium atoms [45] …”
Section: Pt3x Compounds In Orrmentioning
confidence: 99%